Analisis faktor instrumen penyelesaian masalah teknologikal: kajian di sekolah rendah daerah Miri - Anna Felicia,; Sabariah Sharif,; Wong, WK; Muralindran Mariappan, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The purpose of this study is to verify the constructs found in the technological problem solving instrument. The instrument used to measure the technological problem solving is the Technology Problem Solving Inventory (PSI-TECH), derived from the original instrument PSI-PSYCH which consists of three constructs. Exploratory Factor Analysis (EFA); Kaiser-Meyer-Olkin (KMO) and Barlett's analysis were applied for factor analysis in the validity and reliability of the PSI-TECH instrument. The minimum weighting factor is 0.60, used as the cut off value for factor loading. Meanwhile, the Cronbach alpha value 0.70 and above is considered reliable in this study. A total of 102 primary school students, 12 years old were randomly selected among Miri district primary school students in Sarawak. After the survey was carried out, the results of the analysis confirmed that there were three constructs that had been successfully extracted as described in the original PSI-TECH. However, 4 items were dropped from the list. The results of the analysis can provide guidance to researchers in developing this technological problem solving questionnaire, since demographics and geographies tested were diverse. As a result, the findings provide guidance to local researchers in using these instruments.